(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
Optimal conditions of weissellicin production from a local isolate of Weissella cibaria were studied. The sources included carbon sources, nitrogen sources, salts, temperature, pH, incubation time, and inoculum size. The best conditions for producing weissellicin from bacteria were fructose 15%, peptone 0.5%, yeast extract 0.5%, acidic di potassium phosphate 0.15%, incubation temperature of 37°C, pH 5, incubation duration of 48 hours, and initial inoculum volume 1 x 109 cells/ml. Peptone was studied at different concentrations. The best concentration was 1.5%. The yeast extract concentration was also investigated. the best concentration was 1%. The concentration of fructose 2.5% was the best. These concentrations achieved obtaining weissellicin of about 0.848 mg/ml.